VISUALIZATION OF FOOD SECURITY OFFICE DATA, METRO CITY AGRICULTURE AND FISHERIES - Kasmiatun, Kasmiatun; Saputri, Tri Aristi (Institut Bakti Nusantara, 2023)
The Metro City Food Security, Agriculture, and Fisheries Service is the implementing element of the regional government in the fields of Food Security, Agriculture, Livestock, and Fisheries. In its activities, the Metro City Food Security, Agriculture, and Livestock Service has an annual agricultural report in the form of a report book. However, it does not yet have a display of agricultural data that is presented concisely and attractively. This research will visualize the development of agricultural production using Agricultural Report in Figures (PDA) data for 2018-2022 using the cloud data studio application as a tool for managing and visualizing data quickly, easily, and interestingly, from various sources, capable of analyzing data that produces information as Evaluation materials that are easy to review help the leadership's role in making decisions that don't go wrong.